The Impact of Innovation and Foreign Direct Investment (FDI) and Its Interaction to Export Value of High-Technology Products of Asian-10 - Ilmi, Nadia (Universitas Airlangga, 2017)
High-technology product is highly depend on science and technology innovation that leads to renewal or improvement of products and services. Foreign direct investment has spillover effects in the form of transfer of foreign technology, managerial capabilities, and improved international competitiveness for domestic companies. The objectives of the study is to analyze the impact of innovation and Foreign Direct Investment (FDI) on the export of high-technology products Asian-10 countries. This study utilize the gravity model framework and panel dataset from 10 countries in Asian and 29 trading partners country with the period from 2006 to 2013. The results show that innovation of exporter countries, FDI of exporter and importer countries, as well as the interaction between FDI and innovation of exporter countries have a positive and significant impact, and the interaction between FDI and innovation of importer countries have a negative and significant impact on exports of high-technology Asian-10. In this study also found that the innovation of importer countries do not have a significant impact on the export of high-technology products Asian-10 countries from 2006 to 2013. Keywords: Innovation, Foreign Direct Investment, Gravity Model, Export JEL: F1, F2